Tinjauan Yuridis terhadap Efektivitas Arbitrase Internasional dalam Menyelesaikan Sengketa Investasi Asing di Indonesia dan Tantangan Struktural - Faiq Fatih Alwan; Sang Ayu Putu Rahayu (JOURNAL SAINS STUDENT RESEARCH, 2025)
The selection of a dispute resolution forum is a crucial issue in international investment law. International arbitration, especially through institutions such as ICSID and UNCITRAL, is seen as the main means of ensuring effective dispute resolution and legal certainty for foreign investors. This article examines the effectiveness of the implementation of international arbitration in the context of foreign investment dispute resolution in Indonesia using a legal approach and highlights the structural challenges that are still faced in practice. The analysis covers aspects of jurisdiction, enforcement of decisions, and legal and institutional barriers that hinder optimal legal protection for investors. The findings show that although the Indonesian legal framework has accommodated the principles of international arbitration through the ratification of major conventions, its implementation is still not fully effective. The lack of regulatory harmonization, limited institutional capacity, and inconsistent interpretation of public order are the main inhibiting factors. Legal reform and strengthening of law enforcement institutions are needed to create a more conducive investment climate that is in line with international standards.